THE CORELATION BETWEEN THE IMPLEMENTATION OF THERAPEUTIC COMMUNICATION BY HEALTH WORKERS AND THE LEVEL OF PATIENT SATISFACTION IN THE INPATIENT ROOM AT RSUD KABUPATEN BEKASI - S., Christine Margaretha; Baltasar S. S. Dedu; https://orcid.org/0000-0002-5707-0347 (Soscience: Jurnal Ilmu Sosial Science, 2025)
Therapeutic communication was able to affect the level of patient satisfaction. Therapeutic communication is a problem that health workers need to pay attention to. However, it turns out that there are still hospitals that provide or carry out therapeutic communication which are considered not good by patients so that most of the patients who visit the hospital feel less satisfied. Therapeutic communication is something that every health worker must master and possess. This study was conducted to determine the relationship between the implementation of therapeutic communication by health workers with the level of patient satisfaction in the inpatient room at RSUD Kabupaten Bekasi. This research method is a quantitative type that is analytic with a cross sectional approach. The population of this study were patients in the inpatient room at Bekasi District Hospital using probability sampling technique with stratified random sampling. Based on the results of statistical analysis using the chi-square test, the p-value was 0.000 ≤ 0.05. This indicates that H0 is rejected. There is a significantly relationship between the implementation of therapeutic communication by health workers with the level of patient satisfaction in the inpatient room at RSUD Kabupaten Bekasi.